Reexcavando en los museos: Novedades epigráficas en soportes de plomo (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
We present two new leads with Iberic inscriptions, found in the Museu d’Arqueologia de Catalunya-Barcelona and the Museu Torre Balldovina; they are supposed to come from the Puig Castellar Iberian oppidum (Santa Coloma de Gramenet).
Keywords: Epigraphy; Iberian Language; Lead; Sheet ingot; Puig Castellar